Systematic Cluster Head (CH) Selection Through Node-Grade Based Clustering (NGBC) in WSN - K. Deepak Keynes, J.; Shalini Punithavathani, D. (International Journal of Engineering and Technology, 2018)
As it is well known, in Wireless Sensor Networks, the sensor nodes will be either mobile or static. When mobility is concerned, on the whole network performance could be degraded, since the sensor nodes are furnished with restricted battery power, restricted memory, less computational ability and lower range of communication. So, a mechanism which is effective is needed there for forwarding the data packets with efficient energy management and coverage. With that note, the principle target of this work is to propose systematic method of CH selection based on the factors such as low mobility, density of the nodes and their remaining energy. Moreover, an innovative method called Node-Grade Based Clustering (NGBC) is proposed in this paper so as to select the CHs, studying the node’s energy and position regarding to their Base Station (BS), which will act as a sink for collected information. The CHs are replaced in every round based on its duty cycle on sensor nodes and Threshold Energy Rate (TER). Since the BS evaluates the quantity of every round a CH (Cluster Head) can sustain, it minimizes the quantity of energy consumed and increases the WSN’s lifetime. The results of the simulation demonstrate that the proposed algorithm attains higher coverage, efficiency in energy and network lifetime. Furthermore, the performance results in the work which is proposed, are distinguished with the algorithms proposed previously such as LEACH and HEED using some evaluation metrics like packet delivery ratio, throughput, energy consumption and end-to-end delay to prove the efficiency of energy efficient NGBC.